Effect of industrial policies on business attraction - Kowo Solomon Akpoviroro; Akinbola Olufemi Amos; Odumesi Abolaji Oladimeji; Mufutau Akanmu Popoola (Journal of Perspectives in Management, 2023)
Industrial policies in Africa have been characterized with the problem of government. Government has various tools to influence the market, government creates rules and frameworks in which businesses compete against each other from time to time, the government will now change these rules and framework forcing businesses to change the way they operate. Due to these reasons, the objectives of the study were to examine the influence of industrial estate on venture creation, to determine the impact of policy implementation on firm’s production capacity, thirdly, to investigate the effect of public health policy on business growth. The ex-post facto method was employed. The population consists of the employees of pharmaceutical industry in Lagos, Nigeria. Slovin Sample size determination formula was adopted to determine the sample size. The data was analyzed using manual and electronic based methods through the data preparation grid and statistical package for the social sciences, (SPSS). Linear regression and ANOVA method was employed. The study found out that Industrial estate has a positive influence on venture creation such that industrial estate affected venture creation. Findings from hypothesis two shows a positive relationship between policy implementation and firm production capacity. The result of hypothesis three revealed that there is a significant positive relationship between public health policy and business growth. Thus, the study recommends that government should continue to play their regulatory role in the promotion of industrial policies in the country and also business organizations should also obey and implement public health policies.